Oxygen reduction catalysts and applications thereof
Patent Information
- Application Number
- CN202512004883.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-04
- Filing Date
- 2025-12-29
- Publication Date
- 2026-10-16
AI Technical Summary
[0009] According to this oxygen reduction catalyst, the modified layer comprises an organic nitrogen compound having the aforementioned triazine ring structure. By having a large functional group (alkyl group with 3-8 carbon atoms) in the triazine ring structure, the physical contact opportunity between the organic nitrogen compound and the acidic ionomer can be suppressed, thus inhibiting their interaction. This suppresses the decrease in ionomer performance under low humidification conditions. Consequently, the decrease in battery performance is also suppressed.
Smart Images

Figure CN122930935A_ABST
Abstract
Description
Technical Field
[0001] This specification relates to oxygen reduction catalysts and their applications. Background Technology
[0002] It is known that adding organic nitrogen compounds to the catalyst metal used in fuel cells improves the activity of the oxygen reduction reaction in the catalyst and thus improves the power generation efficiency of the fuel cell. Examples of such organic nitrogen compounds include melamine-formaldehyde polymers (Patent Document 1) formed by polymerizing monomers having aldehyde groups.
[0003] Patent Document 1: Japanese Patent Application Publication No. 2024-11754 Summary of the Invention
[0004] However, it is known that in fuel cells, the interaction between acidic ionomers and the basic groups of organic nitrogen compounds reduces the proton conductivity of the ionomers. Under low humidification, this reduces the ionic conductivity or durability of the ionomers, thus reducing the performance of the fuel cell.
[0005] This specification provides a technique to suppress the interaction between organic nitrogen compounds, such as melamine-formaldehyde polymers, added to oxygen reduction reaction catalysts and ionomers, thereby helping to suppress the degradation of ionomer performance under low humidification conditions.
[0006] This specification discloses oxygen reduction catalysts. The oxygen reduction catalyst comprises: a catalyst metal having oxygen reduction reactivity, and a modification layer comprising an organic nitrogen compound or its cation having a triazine ring structure moiety. The triazine ring structure moiety is represented by the following formula (I).
[0007]
[0008] In formula (I), R1, R2, R3, R4, R5, and R6 each independently represent a hydrogen atom, a group represented by R7OCH2-, or a group represented by -X-*. Here, R7 represents a hydrogen atom or an alkyl group with 3 to 8 carbon atoms, X represents a methylene group (-CH2-) or a methyleneoxy group (-O-CH2-), and * represents a bonding site. At least one of R1, R2, R3, R4, R5, and R6 is a group represented by R7OCH2- (R7 being an alkyl group with 3 to 8 carbon atoms).
[0009] According to this oxygen reduction catalyst, the modified layer comprises an organic nitrogen compound having the aforementioned triazine ring structure. By having a large functional group (alkyl group with 3-8 carbon atoms) in the triazine ring structure, the physical contact opportunity between the organic nitrogen compound and the acidic ionomer can be suppressed, thus inhibiting their interaction. This suppresses the decrease in ionomer performance under low humidification conditions. Consequently, the decrease in battery performance is also suppressed. Detailed Implementation
[0010] The oxygen reduction catalyst disclosed in this specification may further comprise the following: In another embodiment of the oxygen reduction catalyst, the organic nitrogen compound comprises a melamine-formaldehyde polymer. Using the aforementioned polymer, the modified layer is tightly bonded and integrated with the catalyst metal.
[0011] Another approach to the aforementioned oxygen reduction catalysts involves using a branched alkyl group as R7. This allows for effective utilization of the large volume while minimizing contact opportunities.
[0012] Another embodiment of the aforementioned oxygen reduction catalyst includes: R7 being a branched alkyl group, and the molar ratio of R7 to the total molar ratio of the triazine rings of the aforementioned organic nitrogen compound being 0.28 or more. This further effectively suppresses the physical contact opportunities between the ionomer and the aforementioned organic nitrogen compound, thereby inhibiting interactions.
[0013] Another approach to the aforementioned oxygen reduction catalysts includes having R7 selected from one or more of isopropyl, sec-butyl, isobutyl, and tert-butyl groups. These functional groups offer a balance between large size and the ability to introduce functional groups.
[0014] Alternatively, the disclosure in this specification may also refer to a cathode for a fuel cell containing the aforementioned oxygen reduction catalyst. It may also refer to a fuel cell equipped with the aforementioned cathode.
[0015] Alternatively, the disclosure in this specification can also refer to an anode for a water electrolysis system containing the aforementioned oxygen reduction catalyst. It can also refer to a water electrolysis system equipped with the aforementioned anode.
[0016] The following describes in detail various embodiments of the oxygen reduction catalyst (hereinafter also referred to as the catalyst) disclosed in this specification.
[0017] The oxygen reduction catalyst disclosed in this specification can be used in fuel cells such as PEFCs, and also in water electrolysis systems. The catalyst disclosed herein can be used as the cathode or anode of a fuel cell, as the anode or cathode of a water electrolysis system.
[0018] The oxygen reduction catalyst disclosed in this specification can be in the form of, for example, catalyst ink, or in a layered form as a so-called electrode. The binder described later may be used as needed.
[0019] (Oxygen reduction catalyst)
[0020] The oxygen reduction catalyst disclosed in this specification comprises a catalyst metal and a modification layer comprising an organic nitrogen compound having a triazine ring structure moiety as shown in Formula (I) or its cation. These elements will be described below.
[0021] (Catalyst metal)
[0022] There are no particular limitations on the catalyst metal contained in the catalyst, as long as it possesses oxygen reduction activity. Examples of catalyst metals include platinum, ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium. One or more of these metals may be used. Additionally, the catalyst metal may be an oxide, nitride, sulfide, or phosphide; one or more of these oxides may be used.
[0023] In the above, the catalyst metal is sometimes preferably one or more selected from platinum, platinum alloys, and platinum-containing composites. Examples of metals other than platinum contained in platinum alloys and platinum-containing composites include ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium, and more than two of these metals may be included. It should be noted that the elemental ratio of metals other than platinum in platinum alloys is not particularly limited and can be from 0.11 to 50 atm%.
[0024] The catalyst metal typically has a particle morphology, and its average particle size is not particularly limited, for example, it is above 1 nm and below 100 nm.
[0025] The catalyst metal can be supported on a carrier. The carrier can be a combination of one or more selected from carbon and oxides. Examples of carbon include conductive carbon, carbon black (acetylene black, Ketjen black, channel black, roller black, disc black, oil furnace black, natural gas furnace black, lampblack, thermal cracking black, and VULCAN (registered trademark) series carbon), activated carbon, lead black, glassy carbon, graphite, graphene, carbon fiber, carbon nanotubes, carbon nitride, carbon sulfide, and carbon phosphide). Two or more of these can also be used in combination. Additionally, oxides can be one or more selected from titanium oxide, niobium oxide, tin oxide, tungsten oxide, and molybdenum oxide, or in combination.
[0026] In addition to primary particles, the carrier can also be secondary particles. There is no particular limitation on the average particle size of primary particles, for example, it can be above 5 nm and below 500 nm.
[0027] (Modification layer)
[0028] To accelerate the oxygen reduction activity of the catalyst metal, a modification layer is provided on the surface of the catalyst metal. The modification layer contains an organic nitrogen compound or its cation. It should be noted that the cation includes cations formed by the dissociation of the basic functional groups of the organic nitrogen compound or cations that form salts with organic or inorganic acids.
[0029] (organic nitrogen compounds)
[0030] Organic nitrogen compounds only need to possess the activity of promoting oxygen reduction activity based on catalyst metals. Organic nitrogen compounds possess the triazine ring structure shown in formula (I). Organic nitrogen compounds can be, for example, any one or more of non-polymer monomers, polymers, or their cations (salts), or combinations of two or more.
[0031]
[0032] In formula (I), R1, R2, R3, R4, R5, and R6 each independently represent a hydrogen atom, a group represented by R7OCH2-, or a group represented by -X-*. Here, R7 represents a hydrogen atom or an alkyl group with 3 to 8 carbon atoms, X represents a methylene group (-CH2-) or a methyleneoxy group (-O-CH2-), and * represents a bonding site. At least one of R1, R2, R3, R4, R5, and R6 is a group represented by R7OCH2- (R7 being an alkyl group with 3 to 8 carbon atoms).
[0033] It should be noted that the bonding site is the bonding site with the triazine structural portion shown in formula (I).
[0034] The R7OCH2- (R7: alkyl group with 3 to 8 carbon atoms) group in the organic nitrogen compound is only required to suppress the opportunity for physical contact with ionomers, etc., and is not particularly limited. For example, the molar number of R7OCH2- groups relative to the total molar number of triazine rings in each organic nitrogen compound is sometimes preferably 0.20 or more. This ensures a large volume around the triazine ring, effectively suppressing the opportunity for physical contact between the organic nitrogen compound and the ionomer. Other examples include 0.28 or more, 0.30 or more, 0.32 or more, 0.34 or more, 0.35 or more, 0.50 or more, 0.60 or more, 0.70 or more, 0.80 or more, 0.90 or more, 1.0 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.8 or more, 2.0 or more, 2.1 or more, and 2.5 or more. Additionally, the values are 4.0 or less, 3.0 or less, 2.5 or less, 2.2 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.8 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, and 0.3 or less. The usage range of the group shown in R7OCH2- can be set within any combination of the above lower and upper limits, for example, it can be 0.28 or more and 2.2 or less, 0.28 or more and 2.1 or less, 0.28 or more and 2.0 or less, 0.30 or more and 2.0 or less, etc.
[0035] The alkyl group having 3 to 8 carbon atoms as R7 is selected independently and appropriately. This alkyl group can be a straight-chain alkyl group or a branched-chain alkyl group, with branched-chain alkyl groups sometimes preferred. Branched-chain alkyl groups have a large volume, thus physically reducing the chance of contact with surrounding ionomers. Alkyl groups having 3 to 8 carbon atoms can be appropriately used as branched-chain alkyl groups. For example, branched-chain alkyl groups having 3 to 6 carbon atoms, 3 to 5 carbon atoms, or 3 to 4 carbon atoms are sometimes preferred. For example, one or more of isopropyl, sec-butyl, isobutyl, and tert-butyl are sometimes preferred. These functional groups combine large volume with good functional group introgression. Isopropyl and isobutyl are also examples.
[0036] When the organic nitrogen compound is a polymer, in addition to the triazine structural moiety described above, it may also contain structural units derived from other monomers. For example, the polymer may contain structural units derived from thiocyanuric acid. Examples of thiocyanuric acid compounds include thiocyanuric acid and its derivatives. Examples of cyanuric acid compounds include cyanuric acid and its derivatives.
[0037] Organic nitrogen compounds can be obtained commercially or by known methods. When the organic nitrogen compound is a polymer, the polymerization conditions can be based on those used for melamine and formaldehyde polymerization, alcohol modification, etc. The degree of polymerization and molecular weight of the polymer are not particularly limited. By encapsulating the polymer in a modification layer, it is firmly adsorbed onto the catalyst metal, thus improving adsorption stability. The degree of polymerization of the polymer can range from 1 to 10,000. It should be noted that the X at the bonding site varies depending on the polymerization conditions, etc.
[0038] Organic nitrogen compounds are not particularly limited; for example, polymers having the following structural units can be cited.
[0039] When the organic nitrogen compound is a polymer, examples of melamine-formaldehyde polymers include the following. At least one of R' represents an alkyl group having 3 to 8 carbon atoms, such as a branched alkyl group having 3 to 8 carbon atoms, a branched alkyl group having 3 to 5 carbon atoms, or a branched alkyl group having 3 to 4 carbon atoms.
[0040]
[0041] There is no particular limitation on the content of organic nitrogen compounds in the catalyst. For example, the total mass of organic nitrogen compounds relative to the mass of the support alone supporting the catalyst metal can be more than 1.0% by mass and less than 15% by mass.
[0042] Here, the mass of the organic nitrogen compounds is obtained by extracting them from the catalyst and determining their mass using chromatographic methods such as HPLC and GC. For compound identification, mass spectrometry, NMR, IR, and UV spectrometry can be used appropriately. Additionally, the mass of the support can be determined by the following method: After removing the organic nitrogen compounds and organic compounds such as binders from the catalyst through solvent separation, a support containing the residual catalyst metal is obtained. The remaining portion obtained by calcining the catalyst metal-supported support to remove the support is then used as the catalyst metal, and the mass of the support is determined based on its mass.
[0043] (Adhesive)
[0044] In addition to these, the catalyst may also contain a binder. The binder is an ionomer possessing acidic or basic functional groups. Sometimes, an ionomer possessing acidic functional groups is preferred. Examples of acidic functional groups include sulfonic acids and phosphoric acids. Examples of basic functional groups include quaternary ammonium cations. The binder may be a perfluorocarbon sulfonic acid polymer, an anion exchange polymer, or a polymer primarily composed of polyetheretherketones and polybenzimidazoles.
[0045] The content of binder in the catalyst is not particularly limited. For example, the mass ratio of binder to support can be 70% by mass or more and 115% by mass or less. The mass of the support is as described above. The mass of the binder is obtained by extracting the binder from the catalyst and determining its mass. Mass spectrometry, NMR, IR, UV, etc., can be appropriately used for the identification of the binder.
[0046] As described above, the catalyst can take the form of catalyst ink, or the form of a catalyst layer after coating with catalyst ink. The formation of catalyst ink and catalyst layer will be explained below.
[0047] (Preparation of catalyst ink)
[0048] First, a predetermined amount of a catalyst metal-supported carrier (catalyst metal support), an organic nitrogen compound, a binder, and a solvent are added to a container, and the mixture is stirred using a stirrer to prepare the catalyst ink. The type of solvent is not particularly limited; any liquid can be used. Examples include alcohols, or a mixture of at least one alcohol and water. Examples of alcohols include methanol, diacetone alcohol, ethanol, 1-propanol, 2-propanol, tert-butanol, ethylene glycol, and propylene glycol.
[0049] There are no particular limitations on the mixer; various well-known mixers can be used. Examples include ultrasonic homogenizers, jet mills, ball mills (such as bead mills), high-shear mixers, and Filmics mixers. There are no particular limitations on mixing conditions such as mixing speed, mixing time, and rotation speed; these can be set appropriately.
[0050] After stirring, perform vacuum degassing and let stand for 1 day. There is no limit to the standing time; it can be set arbitrarily. Alternatively, it can be used without standing. Furthermore, vacuum degassing can be performed again.
[0051] (Catalyst layer fabrication)
[0052] The prepared catalyst ink is coated onto a specified substrate, and the solvent is removed after coating. For example, the catalyst ink is coated onto a substrate, and the coated catalyst ink is heated and dried to remove the solvent.
[0053] There are no particular limitations on the substrate, but examples include polytetrafluoroethylene (PTFE), electrolyte membranes with ion exchange groups, gas diffusion layers (GDL) made of carbon fibers or metal fibers, and gas diffusion layers made of carbon fibers or metal fibers with microporous layers (MPL).
[0054] The coating method can be any method that can uniformly coat the catalyst ink onto the substrate, and examples include molding, spin coating, screen printing, doctor blade coating, scraper coating, spraying, and applicator coating. The heating rate and heating time can be appropriately set according to the type of solvent. Alternatively, the removal rate can be increased by degassing simultaneously with heating. The coating thickness can be 5–30 μm, or it can meet the requirement of a platinum content of 0.1–0.6 mg·cm³. -2 The coating is applied in a specific manner.
[0055] (Catalyst layer)
[0056] According to this specification, an oxygen generation catalyst layer or an oxygen reduction reaction catalyst layer comprising the above-described catalyst can be provided. Since the oxygen reduction reaction of the catalyst metal is reversible, a fuel cell having this catalyst layer as a cathode (oxygen reduction catalyst layer) can also be provided. It should be noted that the fuel cell is, for example, a PEFC. In this fuel cell, the reduction in power generation efficiency caused by the deposition of the modification layer is avoided or suppressed. It should be noted that the structure of the fuel cell other than the cathode is well known to those skilled in the art.
[0057] Furthermore, a water electrolysis system is also provided, in which a catalyst layer comprising the aforementioned catalyst serves as the anode (oxygen generation reaction catalyst layer). In this water electrolysis system, the reduction in water generation efficiency of the water electrolysis device caused by the deposition of the modification layer is avoided or suppressed. It should be noted that the structure of the water electrolysis system other than the anode is well known to those skilled in the art.
[0058] Example
[0059] The following describes embodiments that embody the disclosure of this specification. It should be noted that the following embodiments are for illustrative purposes only and do not limit the scope of the invention.
[0060] Example 1
[0061] A catalyst metal particle support (containing platinum particles, 3-4 nm in diameter) loaded as the catalyst metal, an organic nitrogen compound (melamine-formaldehyde polymer) with a triazine ring structure as shown in Table 1 below, perfluorocarbon sulfonic acid as a binder, and a water-alcohol mixture as a solvent are added to a container in specified amounts. It should be noted that Table 1 shows the type of alkyl group in formula (I) R7 and the ratio of the number of alkyl groups per mole of the triazine ring.
[0062] These materials were mixed and stirred using a mixer (homogenizer, Filmics) to prepare the catalyst inks of Examples 1-5 containing an oxygen reduction catalyst.
[0063] It should be noted that, except for the inclusion of triazine (monomer) that does not use organic nitrogen compounds, triazine that does not have an alkoxy group as an organic nitrogen compound, triazine ring structure with methyl as an alkoxy group, and melamine-formaldehyde polymer having triazine ring structure with isobutyl as an alkoxy group in a specific amount, the catalyst inks of Comparative Examples 1 to 4 were prepared in the same manner as in Example 1.
[0064] It should be noted that the melamine-formaldehyde polymers used in the examples and comparative examples were obtained from Tokyo Chemical Industry Co., Ltd. and Sigma-Aldrich.
[0065] The catalyst ink that has undergone degassing treatment is appropriately coated onto the substrate, and the coated catalyst ink is heated and dried to remove the solvent, thus forming a catalyst layer.
[0066] Next, the prepared catalyst layers were used as cathode catalyst layers, a perfluorocarbon sulfonate polymer (Chemours Nafion NR211, EW: 1100) was used as the electrolyte membrane, and a platinum-supported carbon catalyst (Tanaka Precious Metals Industry TEC10E50E) was used as the anode catalyst layer. The electrolyte membrane was sandwiched between the cathode and anode catalyst layers. Under heating (130°C) and pressurization (3MPa), the cathode catalyst layer, electrolyte membrane, and anode catalyst layer were hot-pressed together. A gas diffusion layer made of carbon fiber (SGL GDL22BB) was placed on the outside of the cathode and anode catalyst layers to fabricate a membrane electrode assembly (MEA) (electrode portion: 1cm × 1cm).
[0067] [Table 1]
[0068]
[0069] Next, the fabricated MEA was used as a single cell to determine its current-voltage characteristics under low humidification conditions (30% RH) and high humidification conditions (80% RH). The measurement conditions were as follows: scan rate: 20 mA / s (anodic scan), cell temperature: 80°C, pressure: 150 kPa (ABS), cathode gas type: air, cathode gas flow rate: 2.0 L / min. It should be noted that current-voltage characteristics can be obtained under arbitrary conditions. The results are shown in Table 1.
[0070] As shown in Table 1, it can be seen that the presence of an alkoxy group in the triazine ring structure can suppress the decrease in battery voltage under low humidification. Furthermore, it can be seen that, compared to straight-chain alkyl groups, alkoxy groups with branched alkyl groups are more effective in suppressing the decrease in battery voltage under low humidification.
[0071] Therefore, it can be seen that the amount of alkoxy group relative to the triazine ring is preferably a certain level or higher. For example, it is 0.28 or higher, and 2 or less.
Claims
1. An oxygen reduction catalyst, comprising: Catalyst metals, which exhibit activity in the oxygen reduction reaction, and A modification layer comprising an organic nitrogen compound or its cation having a triazine ring structure moiety as shown in formula (I), In formula (I), R1, R2, R3, R4, R5, and R6 each independently represent a hydrogen atom, R7OCH2- represents a group, or -X-* represents a group. Here, R7 represents a hydrogen atom or an alkyl group with 3 to 8 carbon atoms, X represents a methylene group (-CH2-) or a methyleneoxy group (-O-CH2-), and * represents a bonding site. At least one of R1, R2, R3, R4, R5, and R6 is a group represented by R7OCH2-, where R7 in R7OCH2- is an alkyl group with 3 to 8 carbon atoms.
2. The oxygen reduction catalyst according to claim 1, wherein, The organic nitrogen compound includes a melamine-formaldehyde polymer.
3. The oxygen reduction catalyst according to claim 1, wherein, In formula (I), R7 is a branched alkyl group.
4. The oxygen reduction catalyst according to claim 1, wherein, In formula (I), R7 is a branched alkyl group, and the ratio of the molar number of R7 in the organic nitrogen compound to the total molar number of the triazine ring is 0.28 or more.
5. The oxygen reduction catalyst according to claim 1, wherein, In formula (I), R7 is one or more selected from isopropyl, sec-butyl, isobutyl and tert-butyl.
6. A cathode for a fuel cell comprising the oxygen reduction catalyst according to any one of claims 1 to 5.
7. A fuel cell comprising the cathode of claim 6.
8. An anode for a water electrolysis system, comprising the oxygen reduction catalyst according to any one of claims 1 to 5.
9. A water electrolysis system comprising the anode as described in claim 8.
Citation Information
Patent Citations
Catalyst
JP2024011754A